Aquinas and the Natural Law. Issue 1 (March 2015) - Seipel, Peter
Abstract Recent decades have seen a shift away from the traditional view that Aquinas's theory of the natural law is meant to supply us with normative guidance grounded in a substantive theory of human nature. In the present essay, I argue that this is a mistake. Expanding on the suggestions of Jean Porter and Ralph McInerny, I defend a derivationist reading of ST I‐II, Q. 94, A. 2 according to which Aquinas takes our knowledge of the genuine goods of human life and their proper ordering to one another to be self‐evident only to the wise who are able to discern the truth about our God‐given human nature. I then show that this reading provides a better account of Aquinas's view than two recent alternatives: John Finnis's brand of inclinationism and Daniel Mark Nelson's virtue‐based interpretation.